Status and groups - Thomas-Hunt, Melissa C.; Wageman, Ruth.; Emerald eBooks (Bingley, U.K. : Emerald, 2005)
This seventh volume of Research on Managing Groups and Teams examines the effects of status on individuals and groups. At the most basic level status describes the rank of individuals or groups within a specified context. It refers to the prestige hierarchy which determines, which individuals or groups are afforded honor and respect and are, consequently, given opportunities to influence outcomes. The authors in this volume consider both the role of status within groups and how the status of groups within their larger context affects members and overall group effectiveness. Consequently, the works presented here consider the relationship between the status of individuals and groups, the treatment they receive, and their participation within their immediate environment; the link between exhibited behaviors and status conferral; and the emergence and effects of status rivalries within and across groups, including challenges to existing status hierarchies. This book will be of particular interest to individuals interested in understanding the effects of status on individuals and the groups and organizations in which they are embedded.
A matter of intragroup status : the importance of respect for the viability of groups / David De Cremer, Tom R. Tyler -- 'I know what I'm doing' : the impact of gender stereotypes about expertise on task assignments in groups / Samuel N. Fraidin, Andrea B. Hollingshead -- Member status and information exchange in decision-making groups / Gwen M. Wittenbaum, Jonathan M. Bowman -- Internal status sorting in groups : the problem of too many stars / Jennifer R. Overbeck, Joshua Correll, Bernadette Park -- Cosmopolitans and locals : status rivalries, deference, and knowledge in international teams / Martine R. Haas -- Here today, gone tomorrow? Effects of nonstandard work status on workgroup processes and outcomes / Heather C. Vough, Joseph P. Broschak, Gregory B. Northcraft -- It's not just about differences : an integration of role identity theory and status characteristics theory / Amy E. Randel, Lee Chay-Hoon, P. Christopher Earley -- The camouflage effect : separating achieved status and unearned privilege in organizations / Ashleigh Shelby Rosette, Leigh Thompson -- From system justification to system condemnation : antecedents of attempts to change power hierarchies / Paul V. Martorana, Adam D. Galinsky, Hayagreeva Rao -- Role of status in group processes / Edward J. Lawler -- A big fish in a small pond or a small fish in a big pond? Importance of intra-versus intergroup status across cultures / Ya-Ru Chen -- Misperceiving your place : humility and hubris in social hierarchies / Cameron P. Anderson, Sandra E. Spataro -- To be smart or to be social? The context-dependent effects of communication styles on status conferral in task groups / Alison R. Fragale -- Preface / Melissa C. Thomas-Hunt.
Keywords: Business & Economics -- General; Social Science -- General; Social, group or collective psychology; Teams in the workplace; Social status; Electronic books